Valproate, risperidone, and paliperidone: A case of valproate-induced hyperammonemic encephalopathy - Kyle Wesselman, PharmD candidate, MA, BS; Vincent Cavaliere, PharmD, MM, BCPP; Rakesh Goyal, MD; Eric Anderson, MD, MBA, FAPA (American Association of Psychiatric Pharmacists, 2024)
Hyperammonemia is a well-known adverse effect of valproate that can progress to a potentially fatal condition known as valproate-induced hyperammonemic encephalopathy (VHE). VHE is more common when valproate is used in combination therapy with other antiepileptic medications. A growing number of case reports have pointed to a possible interaction with the antipsychotic risperidone leading to an increased risk of VHE. We present a case of VHE in which a 20-year-old male patient with bipolar affective disorder developed VHE when on concomitant valproate, risperidone, and paliperidone palmitate. On the seventh day of treatment with oral risperidone, oral divalproex sodium was added. Intramuscular paliperidone palmitate was initiated on day 13, and oral risperidone was discontinued after the second loading dose on day 16. The following day, the patient displayed worsening psychomotor retardation, swaying gait, drowsiness, and vomiting. The patient was found to have hyperammonemia and transferred to the emergency department for treatment of suspected VHE.